Increasing Students' Ability In Writing Procedure Text Through Learning Model Pictures And Pictures - Dina Syarifah Nasution; Muhammad Hasyimsyah Batubara; Rahmayana Rahmayana (Asosiasi Dosen Perguruan Tinggi Islam, 2021)
This study investigated increasing students' ability to write procedure text through learning model pictures and pictures in ninth grade at SMPN 4 Takengon. The study used the quantitative method with experimental design. To collect the data, the writer uses the test (pre-test and post-test). The population in this research is all students of the ninth grade in SMPN 4 Takengon, which consists of 196 students. The writer uses purposive sampling to take the sample in this research. A first group is an experimental group, which amounts to 37 students, and the second group is the control group which amounts to 37 students. The writer uses the t-test formula to analyze data in this research. The result of tscore is 5,71. Compared with the ttable, the tscore is higher, i.e., 5,71, than ttable is 1,99. It can be concluded that learning model pictures and pictures can increase students' ability in writing procedure text. The writer suggests that students try to write in English as habitual because it can help add more vocabulary and make the students have good writing.